2016
DOI: 10.1371/journal.pone.0167827
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Foot and Ankle Using Pedicled or Free Flaps: Perioperative Flap Survival Analysis

Abstract: ObjectiveThe purpose of this study is to determine the correlation between non-technical risk factors and the perioperative flap survival rate and to evaluate the choice of skin flap for the reconstruction of foot and ankle.MethodsThis was a clinical retrospective study. Nine variables were identified. The Kaplan-Meier method coupled with a log-rank test and a Cox regression model was used to predict the risk factors that influence the perioperative flap survival rate. The relationship between postoperative wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…The free ALT flap was reviewed in 72 patients who underwent reconstruction with defects ( Table 4) at the heel, foot and ankle region. We reviewed the ALT flap in three separate studies: for the effectiveness of free flaps in plantar ulcers of the insensate foot, for analysis of perioperative flap survival in reconstruction of the foot and ankle, and to evaluate the relationship between free flap success and postoperative ambulation in diabetic foot limb salvage [9,12,17]. Twenty-five patients underwent reconstruction with 26 free flaps for plantar ulcers of the insensate foot using the ALT (n = 18), RAF (n = 4) and GM (n = 4).…”
Section: Anterolateral Thigh Flapmentioning
confidence: 99%
See 2 more Smart Citations
“…The free ALT flap was reviewed in 72 patients who underwent reconstruction with defects ( Table 4) at the heel, foot and ankle region. We reviewed the ALT flap in three separate studies: for the effectiveness of free flaps in plantar ulcers of the insensate foot, for analysis of perioperative flap survival in reconstruction of the foot and ankle, and to evaluate the relationship between free flap success and postoperative ambulation in diabetic foot limb salvage [9,12,17]. Twenty-five patients underwent reconstruction with 26 free flaps for plantar ulcers of the insensate foot using the ALT (n = 18), RAF (n = 4) and GM (n = 4).…”
Section: Anterolateral Thigh Flapmentioning
confidence: 99%
“…In this study, the ALT flap was regarded as the first choice for reconstruction of plantar ulcers due to having a dual advantage of both a fasciocutaneous and muscle flap providing a stable walking surface while the RAF is preferred for defects at the metatarsal heads and forefoot and GM flaps for defects where obliteration of the dead space is necessary such as in cases of osteomyelitis [9]. In a study of 144 patients, 14 different flaps ( Table 4) were reviewed to determine the correlation between nontechnical risk factors and the perioperative flap survival rate in regards to evaluating the choice of free or pedicled flaps for reconstruction of the foot and ankle [12]. The perioperative period was defined as within 2 weeks after flap transfer.…”
Section: Anterolateral Thigh Flapmentioning
confidence: 99%
See 1 more Smart Citation
“…However, partial or total flap necrosis remains the main complication and has a relatively high incidence . Most studies regarding risk factors of flap necrosis have focused on the risk factors of pedicled flaps of the lower extremities and free flaps . Gir et al .…”
Section: Introductionmentioning
confidence: 99%
“…17 Most studies regarding risk factors of flap necrosis have focused on the risk factors of pedicled flaps of the lower extremities and free flaps. [18][19][20][21][22][23][24][25][26] Gir et al found that age, gender, aetiology or location of the defect, and type or size of the flap were not statistically significant risk factors associated with complications of pedicled perforator flaps in the lower extremities, 24 whereas Bekara et al found that age older than 60 years, diabetes and arteriopathy are significant risk factors for perforator-pedicled flap complications in the lower extremities. 21 In addition, de Blacam et al stated that venous insufficiency and increasing age were both risk factors for pedicled flap complications.…”
Section: Introductionmentioning
confidence: 99%